Sustainability Study of Horticultural Development in Mandailing Natal District With RAPFISH-MDS Analysis - Agung Budi Santoso; Erpina Delina Manurung; Deddy Romulo Siagian; Hendri Ferianson P Purba; Perdinanta Sembiring (Universitas Panji Sakti, 2023)
Mandailing Natal district as the second largest district in North Sumatra Province has great potential for horticultural development. This study aimed to determine the sustainability level of horticultural development in Mandailing Natal district through 5 dimensions, namely ecological, economic, social, technological and institutional. The RAPFISH-MDS analysis method was used to measure the index and sustainability status. The results showed that the criteria for the sustainability of horticultural development in Mandailing Natal district was quite sustainable (52.61) with the sustainability index value of the ecological, institutional, social, economic and technological dimensions, respectively, 58.06; 56.86; 53.76; 51.99; and 51.08. Sensitive attributes supporting sustainability are erosion rate for the ecological dimension, post harvest management for the economic dimension, extension intensity for the social dimension, land management technology for the technological dimension, and conflicts between farmer groups for the institutional dimension. The realization of horticultural development can be through the development of government programs and extensions that change farmers' perceptions of the environment and the application of eco friendly technologies in their farming.